2019
DOI: 10.3144/expresspolymlett.2019.38
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of phthalonitrile-based resin containing benzoxazine and cyanate ester: Curing behaviors, fiber-reinforced composite laminates and improved properties

Abstract: Curing behaviors and copolymerization mechanisms between phthalonitrile-based resin containing benzoxazine (A-ph) and cyanate ester (CE) were characterized and discussed. Results indicated that copolymerization between A-ph and CE were comprised of ring-opening polymerization of oxazine rings and ring-forming polymerization of cyanate and nitrile groups. From them, ring-opening of oxazine occurred preferentially, followed by ring-forming of cyanate and nitrile groups, which were promoted by active hydrogen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…On the other hand, prior works have reported that the Bz‐based polymeric blends do not always promote the flexural strength of their composites. For example, the flexural strength increases as an increased amount of incorporated poly(resorcinol borate), 21 while the amount of incorporated phthalonitrile has minimal influence to its flexural strength 9 . In comparison, an increased amount of incorporated poly (ether‐thioureas) deteriorates the Bz/GF composite's flexural strength 42 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, prior works have reported that the Bz‐based polymeric blends do not always promote the flexural strength of their composites. For example, the flexural strength increases as an increased amount of incorporated poly(resorcinol borate), 21 while the amount of incorporated phthalonitrile has minimal influence to its flexural strength 9 . In comparison, an increased amount of incorporated poly (ether‐thioureas) deteriorates the Bz/GF composite's flexural strength 42 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, the flexural strength increases as an increased amount of incorporated poly(resorcinol borate), 21 while the amount of incorporated phthalonitrile has minimal influence to its flexural strength. 9 In comparison, an increased amount of incorporated poly (ether-thioureas) deteriorates the Bz/GF composite's flexural strength. 42 In Figures 9 and 10, Bz-a shows increased flexural strength and modulus by 27.1% and 13.7%, respectively, for its enhanced interfacial adhesion due to higher cross-linked density of Bz.…”
Section: Interlaminar Shear Strength Of Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Bisphenol-A dicyanate ester is an important high-performance thermosetting polymer with excellent dimensional stability, high heat resistance, low dielectric constant, strong adhesion and good mechanical properties. 1 7 It is usually used as a resin matrix for advanced composites, adhesives and coatings used in the electronics, aerospace and military industries. 8 10 To meet the process requirements of these practical applications, it is necessary for bisphenol-A dicyanate ester to have good processability, including film-forming properties, melting fluidity and a wide processing window.…”
Section: Introductionmentioning
confidence: 99%
“…To deal with the carbon residue problem, it is effective to add a polymer resin which is of high carbon content, into the silicone rubber–inorganic filler composites. Benzoxazine resins (BZs) are a type of highly cross-linked aromatic polymer with outstanding advantages, including excellent thermal resistance, good flame retardancy, and near-zero volumetric shrinkage upon curing and high carbon residue [13,14,15,16]. These extraordinary properties make BZs the ideal resin to be used in SR composites for ultra-high temperature applications.…”
Section: Introductionmentioning
confidence: 99%